Interaction of Wnt Signaling with BMP/Smad Signaling during the Transition from Cell Proliferation to Myogenic Differentiation in Mouse Myoblast-Derived Cells - Kumiko Terada; Satomi Misao; Naoki Katase; Shin-ichiro Nishimatsu; Tsutomu Nohno (International Journal of Cell Biology)
Background. Wnt signaling is involved in muscle formation through β-catenin-dependent or -independent pathways, but interactions with other signaling pathways including transforming growth factor β/Smad have not been precisely elucidated. Results. As Wnt4 stimulates myogenic differentiation by antagonizing myostatin (GDF8) activity, we examined the role of Wnt4 signaling during muscle differentiation in the C2C12 myoblast cell line. Among several extrinsic signaling molecules examined in a microarray analysis of C2C12 cells during the transition from cell proliferation to differentiation after mitogen deprivation, bone morphogenetic protein 4 (BMP4) expression was prominently increased. Wnt4 overexpression had similar effects on BMP4 expression. BMP4 was able to inhibit muscle differentiation when added to the culture medium. BMP4 and noggin had no effects on the cellular localization of β-catenin induced by Wnt3a; however, the BMP4-induced phosphorylation of Smad1/5/8 was enhanced by Wnt4, but not by Wnt3a. The BMP antagonist noggin effectively stimulated muscle differentiation through binding to endogenous BMPs, and the effect of noggin was enhanced by the presence of Wnt3a and Wnt4. Conclusion. These results suggest that BMP/Smad pathways are modified through Wnt signaling during the transition from progenitor cell proliferation to myogenic differentiation, although Wnt/β-catenin signaling is not modified with BMP/Smad signaling.